Implementation of Solar-Powered Submersible Pump Technology (PSTSP) to Increase Rainfed Rice Field Production - Hariyanto Hariyanto; Muhamad Rusdi; Jayadi Jayadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Waninggap Miraf is one of the villages with its main source of income being rice cultivation. Rainfed rice fields are managed by relying on rainwater stored in reservoirs, requiring Alkon pumps to control and supply water. However, operational costs for irrigating the fields have increased due to using oil-based fuels in the Alkon pumps. The implementation of Portable Solar-Powered Submersible Pump Technology (PSTSP) is expected to solve the challenges farmers face. The method utilized is harnessing solar energy as an alternative to oil-based fuels. The dissemination of this technology aims to optimize operational costs and enhance farmers' knowledge of utilizing renewable energy in agriculture. The implementation of this community-driven project involves the participation of the local community in the process of socialization, planning, design, training, and technology application. Based on trial results, this project has successfully increased farmers' knowledge and reduced operational costs by sustaining for up to 4 hours, supplying approximately 12,000 liters of water per hour.